Lithium manganese iron phosphate material and preparation method thereof
Through a simplified preparation method, including sand grinding of multiple manganese sources, mixing of carbon sources, spraying and heat treatment, the complex and cost-effective preparation method of lithium manganese iron phosphate material is solved, and the excellent electrochemical performance of the material is achieved and high compaction density, and reduce production costs, suitable for industrial large-scale production.
Patent Information
- Application Number
- CN202411360521.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-09-26
AI Technical Summary
In the prior art, the preparation method of lithium manganese iron phosphate material has problems such as complex equipment and processes, high production costs and difficulty in achieving large-scale industrial production.
A preparation method including steps S1 to S4 is adopted: In step S1, raw materials including iron source, first manganese source, second manganese source, third manganese source and phosphorus source are sand-milled to obtain the sand-milled material; In step S2, the sand-milled material is mixed with the carbon source to obtain a mixture; in step S3, the mixture is sprayed to obtain a spray material, the spray material is mixed with the lithium source to obtain a mixed lithium yellow material; in step S4, an inert atmosphere The mixed lithium yellow material was heat treated and crushed in turn to obtain lithium manganese iron phosphate material.
The lithium manganese iron phosphate material prepared by this method has excellent electrochemical properties and high compaction density, which simplifies equipment and processes, reduces production costs, and makes it suitable for industrial large-scale production.
Smart Images

Figure CN119461296A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a lithium manganese iron phosphate material and a preparation method thereof. Background Art
[0002] Lithium iron manganese phosphate LiMn x Fe y PO4(LMFP) is an important and cost-effective cathode material in lithium-ion batteries, which has a higher operating voltage than LiFePO4(LFP) and has higher safety compared with layered oxide cathodes. However, due to the lack of an effective synthesis process to solve the problem of Li + Their commercial applications remain challenging due to their slow diffusion kinetics and complex phase transitions.
[0003] Lithium manganese iron phosphate with olivine structure + Only one-dimensional diffusion can be carried out along the plane direction, and charge transfer also mainly occurs on this plane, resulting in an extremely low lithium ion diffusion coefficient. Therefore, adjusting the particle size and ensuring that the diffusion plane orientation is short are of great significance for improving the performance of lithium manganese iron phosphate materials. When the size of lithium manganese iron phosphate material particles is nanometer-scale, the lithium ion migration path is shortened and the migration rate is accelerated. At the same time, the lithium manganese iron phosphate material is fully in contact with the electrolyte, so that the lithium manganese iron phosphate material exhibits better discharge specific capacity, thereby obtaining excellent electrochemical performance.
[0004] The current nano-sizing strategy is mainly achieved through two processes: one is to control the slurry D50 to a particle size far lower than that of the lithium iron phosphate slurry during the slurry sand milling process; the other is to synthesize through a two-step sintering process. The former requires adding more sand mills and grinding times or replacing sand mills with higher particle size requirements; the latter adds the process of sand milling, spraying, and sintering, which is cumbersome and complex to control.
[0005] Although the nano-sizing strategy can shorten the ion transmission particle size and improve the activity of lithium iron manganese phosphate materials, it also puts higher requirements on the equipment and process for producing lithium iron manganese phosphate, thus hindering the low-cost, large-scale industrial production of lithium iron manganese phosphate materials. Summary of the invention
[0006] The main purpose of the present invention is to provide a lithium iron manganese phosphate material and a preparation method thereof, so as to solve the problems of the preparation method of lithium iron manganese phosphate material in the prior art, such as complex equipment and process, high production cost and difficulty in realizing industrial large-scale production.
[0007] In order to achieve the above-mentioned purpose, according to one aspect of the present invention, a method for preparing a lithium iron manganese phosphate material is provided, the preparation method comprising step S1, sand-grinding a raw material comprising an iron source, a first manganese source, a second manganese source, a third manganese source and a phosphorus source to obtain a sand-grinded material; step S2, mixing the sand-grinded material with a carbon source to obtain a mixture; step S3, spraying the mixture to obtain a spray material, mixing the spray material with a lithium source to obtain a mixed lithium yellow material; step S4, in an inert atmosphere, heat-treating and pulverizing the mixed lithium yellow material in sequence to obtain a lithium iron manganese phosphate material; wherein the first manganese source is an inorganic water-soluble manganese compound, the second manganese source is an organic manganese source, and the third manganese source is a manganese oxide.
[0008] Furthermore, in the above step S1, the first manganese source is selected from any one or more of manganese sulfate, manganese nitrate, manganese chloride and manganese dihydrogen phosphate; and / or the second manganese source is selected from any one or more of manganese oxalate, manganese acetate, manganese citrate, manganese glycinate and manganese gluconate; and / or the third manganese source is selected from any one or more of manganese oxide, manganese dioxide, manganese trioxide and manganese tetraoxide.
[0009] By preferably selecting the types of the above three different manganese sources within the above range, it is helpful to further exert the synergistic coordination between the crystal structures and morphologies of the three different manganese sources, thereby improving the grading between different manganese source particles, thereby making the lithium manganese iron phosphate material have a higher compaction density, and at the same time, it is beneficial to improve the efficiency of sand grinding.
[0010] Furthermore, the molar ratio of the manganese element in the first manganese source, the second manganese source and the third manganese source is (1-3): (3-5): (4-6).
[0011] By controlling the molar ratio of the three different manganese sources within the above range, the compaction degree of the material can be improved while better promoting the formation of particle gradation.
[0012] Furthermore, the D50 particle size of the material after sand grinding is 0.48 μm to 0.50 μm.
[0013] By controlling the D50 particle size of the material after sand grinding within the above range, it has an important impact on improving the performance of the lithium iron manganese phosphate material; specifically, it can effectively shorten the migration path of lithium ions, accelerate the migration rate of lithium ions, and at the same time increase the contact area between the lithium iron manganese phosphate material and the electrolyte, showing a better discharge specific capacity, so that the lithium iron manganese phosphate material obtains excellent electrochemical properties; at the same time, the compaction of the lithium iron manganese phosphate material is improved.
[0014] Furthermore, in the above step S1, the raw material further includes a first solvent, and the first solvent is selected from any one or more of water, ethanol, methanol and glycerol; and / or the solid content of the raw material is 30% to 50%.
[0015] By controlling the solid content of the raw materials within the above range, it is helpful to make the iron source, the first manganese source, the second manganese source, the third manganese source, and the phosphorus source uniformly dispersed in the first solvent, and it is also helpful to ensure that the viscosity of the material after sand grinding is within a suitable range, thereby helping to improve the uniform dispersion and stability of the lithium manganese iron phosphate material. Preferably, the first solvent is selected from any one or more of water, ethanol, methanol and glycerol, so as to help improve the solubility of the iron source, manganese source and phosphorus source therein, and at the same time help to improve the stability of the material during the grinding process, prevent agglomeration, and thus obtain a lithium manganese iron phosphate material with a more uniform particle size distribution.
[0016] Furthermore, in the above step S1, the phosphorus source is selected from any one or more of phosphoric acid, diammonium dihydrogen phosphate, diammonium hydrogen phosphate and phosphorus pentoxide; and / or the iron source is selected from any one or more of ferric phosphate, ferric phosphate, ferric oxalate, ferric oxide, ferrous oxide, ferric hydroxide, ferrosoferric oxide and ferric acetate.
[0017] By preferably selecting the above types of phosphorus sources, it is helpful to achieve a more complete mixing between the phosphorus source and the iron source, the first manganese source, the second manganese source, and the third manganese source, and the particle size and morphology of the lithium manganese iron phosphate material can be effectively controlled, thereby improving its charge and discharge performance and cycle stability.
[0018] Furthermore, in the above step S2, the carbon source includes a first carbon source and a second carbon source; the mass ratio of the first carbon source to the second carbon source is (6-8): (2-4), and / or the first carbon source is selected from any one or more of glucose, sucrose, maltose, starch and fructose; and / or the second carbon source is selected from any one or more of citric acid, tannic acid, ascorbic acid, polyacrylic acid, polyvinyl alcohol, xylitol and polyethylene glycol.
[0019] In the present application, by adding a soluble composite carbon source and controlling the mass ratio of the first carbon source to the second carbon source within the above range, it is helpful to utilize the different carbonization temperatures of the first carbon source and the second carbon source, thereby forming a more uniform carbon coating conductive network on the surface of the lithium manganese iron phosphate material, thereby significantly improving the electronic conductivity of the carbon coating layer, and also helping to achieve nano-sizing of the lithium manganese iron phosphate material.
[0020] Furthermore, in the above step S2, the mixture further comprises a second solvent, and the second solvent is selected from any one or more of water, ethanol, methanol and isopropanol; and / or the solid content of the mixture is 30% to 50%.
[0021] The preferred type of the second solvent helps to improve the uniformity of dispersion of the sand-milled material and the carbon source therein, and by controlling the solid content of the mixture within the above range, it helps to ensure that the viscosity of the mixture is within an appropriate range, thereby facilitating the improvement of the uniform dispersion and stability of the lithium manganese iron phosphate material.
[0022] Further, in the above step S4, the heat treatment includes low-temperature heat treatment, medium-temperature heat treatment and high-temperature heat treatment performed in sequence; and / or the heating rate during the heat treatment process is 60℃ / h~180℃ / h; and / or the temperature of the low-temperature heat treatment is 100℃~200℃, and the time of the low-temperature heat treatment is 1h~2h; and / or the temperature of the medium-temperature heat treatment is 450℃~650℃, and the time of the medium-temperature heat treatment is 3h~5h; and / or the temperature of the high-temperature heat treatment is 700℃~750℃, and the time of the high-temperature heat treatment is 5h~8h.
[0023] The above preferred low-temperature heat treatment conditions help to improve the dehydration efficiency and effect of the mixed lithium yellow material; the above preferred medium-temperature heat treatment conditions help to improve the efficiency and effect of lithium iron manganese phosphate phase formation; the above preferred high-temperature heat treatment conditions help to improve the crystallinity of lithium iron manganese phosphate.
[0024] According to another aspect of the present invention, a lithium iron manganese phosphate material is provided. The lithium iron manganese phosphate material is prepared by the aforementioned preparation method.
[0025] The technical solution of the present invention is applied. The present application is based on the diffusion difference between manganese ions and iron ions in the olivine skeleton structure during the heat treatment process (iron ions are integrated into the manganese source). On the one hand, by adopting three manganese sources with different crystal structures and morphologies, a lithium iron manganese phosphate material with excellent electrical properties and high compaction density is prepared through a one-time sand milling and a one-time sintering process, thereby improving the performance of the lithium iron manganese phosphate material while also being beneficial to the formation of particle grading and the improvement of sand milling efficiency; on the other hand, mixing the carbon source alone with the sand milled slurry can avoid the problem of carbon source coating on the particle surface hindering the effective collision of zirconium balls and the reduction of grinding efficiency caused by the thickening of the slurry during grinding; on the other hand, mixing the lithium source with the spray material can avoid the problem of unstable particle size monitoring caused by the combination of lithium ions and phosphate to form precipitates, and can ensure the accuracy of the particle size test of the material after sand milling; therefore, the preparation method of the present application does not require high requirements for the sand mill, nor does it produce high energy consumption such as the two-step process, that is, the preparation method and equipment of the lithium iron manganese phosphate material in the present application are simple, lower cost, and more conducive to industrial large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0027] Figure 1 The SEM image of a lithium manganese iron phosphate material prepared according to Example 1 of the present invention is shown;
[0028] Figure 2 A comparison diagram of compaction density curves of lithium iron manganese phosphate materials prepared according to Example 1 of the present invention and Comparative Examples 1 to 3 is shown. DETAILED DESCRIPTION
[0029] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.
[0030] As analyzed in the background technology, the preparation method of lithium iron manganese phosphate material in the prior art has the problems of complex equipment and process, high production cost and difficulty in realizing industrial large-scale production. To solve this problem, the present invention provides a lithium iron manganese phosphate material and a preparation method thereof.
[0031] In a typical embodiment of the present application, a method for preparing a lithium iron manganese phosphate material is provided, and the preparation method comprises: step S1, sand-grinding a raw material including an iron source, a first manganese source, a second manganese source, a third manganese source and a phosphorus source to obtain a sand-grinded material; step S2, mixing the sand-grinded material with a carbon source to obtain a mixture; step S3, spraying the mixture to obtain a spray material, mixing the spray material with a lithium source to obtain a mixed lithium yellow material; step S4, in an inert atmosphere, sequentially heat-treating and pulverizing the mixed lithium yellow material to obtain a lithium iron manganese phosphate material; wherein the first manganese source is an inorganic water-soluble manganese compound, the second manganese source is an organic manganese source, and the third manganese source is a manganese oxide.
[0032] The present application is based on the diffusion difference between manganese ions and iron ions in the olivine skeleton structure during heat treatment (iron ions are integrated into the manganese source). On the one hand, by adopting three manganese sources with different crystal structures and morphologies, a lithium iron manganese phosphate material with excellent electrical properties and high compaction density is prepared through a one-time sand milling and a one-time sintering process, thereby improving the performance of the lithium iron manganese phosphate material while also being beneficial to the formation of particle grading and the improvement of sand milling efficiency; on the other hand, mixing the carbon source alone with the sand milled slurry can avoid the problem of carbon source coating on the particle surface hindering the effective collision of zirconium balls and the reduction of grinding efficiency caused by slurry thickening during grinding; on the other hand, mixing the lithium source with the spray material can avoid the problem of unstable particle size monitoring caused by the combination of lithium ions and phosphate to form precipitates, and can ensure the accuracy of the particle size test of the material after sand milling; therefore, the preparation method of the present application does not require high requirements for the sand mill, nor does it produce high energy consumption such as the two-step process, that is, the preparation method and equipment of the lithium iron manganese phosphate material in the present application are simple, lower cost, and more conducive to industrial large-scale production.
[0033] In one embodiment of the present application, in the above step S1, the first manganese source is selected from any one or more of manganese sulfate, manganese nitrate, manganese chloride and manganese dihydrogen phosphate; and / or the second manganese source is selected from any one or more of manganese oxalate, manganese acetate, manganese citrate, manganese glycinate and manganese gluconate; and / or the third manganese source is selected from any one or more of manganese oxide, manganese dioxide, manganese trioxide and manganese tetraoxide.
[0034] Preferably, the types of the first manganese source, the second manganese source and the third manganese source are within the above range, which helps to further exert the synergistic coordination between the crystal structures and morphologies of the three different manganese sources, thereby improving the grading between different manganese source particles, thereby making the lithium manganese iron phosphate material have a higher compaction density, and at the same time, it is beneficial to improve the efficiency of sand grinding.
[0035] In one embodiment of the present application, the molar ratio of manganese element in the first manganese source, the second manganese source and the third manganese source is (1-3): (3-5): (4-6).
[0036] By controlling the molar ratio of the first manganese source, the second manganese source and the third manganese source within the above range, the compaction degree of the material can be improved while better promoting the formation of particle grading.
[0037] In one embodiment of the present application, the D50 particle size of the material after sand grinding is 0.48 μm to 0.50 μm.
[0038] By controlling the D50 particle size of the material after sand grinding within the above range, it has an important impact on improving the performance of the lithium iron manganese phosphate material; specifically, it can effectively shorten the migration path of lithium ions, accelerate the migration rate of lithium ions, and at the same time increase the contact area between the lithium iron manganese phosphate material and the electrolyte, showing a better discharge specific capacity, so that the lithium iron manganese phosphate material obtains excellent electrochemical properties; at the same time, the compaction of the lithium iron manganese phosphate material is improved.
[0039] In one embodiment of the present application, in the above step S1, the raw material further includes a first solvent, and the first solvent is selected from any one or more of water, ethanol, methanol and glycerol; and / or the solid content of the raw material is 30% to 50%.
[0040] By controlling the solid content of the raw materials within the above range, it is helpful to make the iron source, the first manganese source, the second manganese source, the third manganese source, and the phosphorus source uniformly dispersed in the first solvent, and it is also helpful to ensure that the viscosity of the material after sand grinding is within a suitable range, thereby helping to improve the uniform dispersion and stability of the lithium manganese iron phosphate material. Preferably, the first solvent is selected from any one or more of water, ethanol, methanol and glycerol, so as to help improve the solubility of the iron source, manganese source and phosphorus source therein, and at the same time help to improve the stability of the material during the grinding process, prevent agglomeration, and thus obtain a lithium manganese iron phosphate material with a more uniform particle size distribution.
[0041] In one embodiment of the present application, in the above step S1, the phosphorus source is selected from any one or more of phosphoric acid, diammonium phosphate, diammonium hydrogen phosphate and phosphorus pentoxide; and / or the iron source is selected from any one or more of ferric phosphate, ferric oxalate, ferric oxide, ferrous oxide, ferric hydroxide, ferroferric oxide and ferric acetate.
[0042] The above-mentioned types of phosphorus sources are all soluble. The present application prefers the above-mentioned types of phosphorus sources, which can not only help to achieve more complete mixing between the phosphorus source and the iron source, the first manganese source, the second manganese source, and the third manganese source, but also effectively control the particle size and morphology of the lithium manganese iron phosphate material, thereby improving its charge and discharge performance and cycle stability.
[0043] In one embodiment of the present application, in the above step S2, the carbon source includes a first carbon source and a second carbon source; the mass ratio of the first carbon source to the second carbon source is (6-8): (2-4), and / or the first carbon source is selected from one of glucose, sucrose, maltose, starch and fructose, and the second carbon source is selected from any one or more of citric acid, tannic acid, ascorbic acid, polyacrylic acid, polyvinyl alcohol, xylitol and polyethylene glycol.
[0044] In the present application, by adding a soluble composite carbon source and controlling the mass ratio of the first carbon source to the second carbon source within the above range, it is helpful to utilize the different carbonization temperatures of the first carbon source and the second carbon source, thereby forming a more uniform carbon coating conductive network on the surface of the lithium manganese iron phosphate material, thereby significantly improving the electronic conductivity of the carbon coating layer, and also helping to achieve the nano-sizing of the lithium manganese iron phosphate material. The nano-scale lithium manganese iron phosphate material has a shorter ion diffusion path and a larger specific surface area, thereby improving the comprehensive electrochemical performance of the lithium manganese iron phosphate material.
[0045] In one embodiment of the present application, in the above step S2, the mixture further includes a second solvent, and the second solvent is selected from any one or more of water, ethanol, methanol and isopropanol; and / or the solid content of the mixture is 30% to 50%.
[0046] The preferred type of the second solvent helps to improve the uniformity of dispersion of the sand-milled material and the carbon source therein, and by controlling the solid content of the mixture within the above range, it helps to ensure that the viscosity of the mixture is within an appropriate range, thereby facilitating the improvement of the uniform dispersion and stability of the lithium manganese iron phosphate material.
[0047] In one embodiment of the present application, in the above-mentioned step S4, the heat treatment includes low-temperature heat treatment, medium-temperature heat treatment and high-temperature heat treatment performed in sequence; and / or the heating rate during the heat treatment process is 60℃ / h~180℃ / h; and / or the temperature of the low-temperature heat treatment is 100℃~200℃, and the time of the low-temperature heat treatment is 1h~2h; and / or the temperature of the medium-temperature heat treatment is 450℃~650℃, and the time of the medium-temperature heat treatment is 3h~5h; and / or the temperature of the high-temperature heat treatment is 700℃~750℃, and the time of the high-temperature heat treatment is 5h~8h.
[0048] The above preferred low-temperature heat treatment conditions help to improve the dehydration efficiency and effect of the mixed lithium yellow material; the above preferred medium-temperature heat treatment conditions help to improve the efficiency and effect of lithium iron manganese phosphate phase formation; the above preferred high-temperature heat treatment conditions help to improve the crystallinity of lithium iron manganese phosphate.
[0049] In another typical embodiment of the present application, a lithium iron manganese phosphate material is provided. The lithium iron manganese phosphate material is prepared by the aforementioned preparation method.
[0050] The lithium manganese iron phosphate material prepared by the above preparation method in the present application has excellent electrical properties and high compaction performance.
[0051] The beneficial technical effects of the present application will be described below in combination with specific embodiments and comparative examples.
[0052] Example 1
[0053] 4 mol of ferric phosphate, 1.2 mol of manganese sulfate, 2.4 mol of manganese acetate and 0.8 mol of manganese tetraoxide were dissolved in deionized water to prepare a 35% solid content liquid (I); 15% of the carbon source (glucose: polyethylene glycol 6000: citric acid = 7.2:1.8:1) of the above raw materials was weighed and dissolved in deionized water to form a 35% liquid (II); the liquid (I) was sand-milled by a sand mill to obtain a sand-milled material, and the particle size D50 of the sand-milled material was controlled to be 0.48-0.50 μm; the sand-milled material and the liquid (II) were mixed by a high-speed disperser for 1 hour and then spray-dried to obtain spray material; mixing the spray material with 10.15 mol of lithium hydroxide by a high mixer for 2 hours to obtain a mixed lithium yellow material; transferring the mixed lithium yellow material into a box furnace for sintering to obtain a sintered powder, specifically, the average oxygen content during the sintering process is less than 10 ppm, the heating rate is 180°C / h, during the low-temperature heat treatment, the temperature is increased to 150°C and kept for 2 hours, during the medium-temperature heat treatment, the temperature is continuously increased to 600°C and kept for 5 hours, during the high-temperature heat treatment, the temperature is continuously increased to 720°C and kept for 5 hours; after the material is cooled to 50°C, it is air flow crushed, and the particle size D50 is controlled to be 0.8-1 μm to obtain a lithium manganese iron phosphate material.
[0054] Example 2
[0055] The difference from Example 1 is that the manganese source uses 1.2 mol of manganese chloride, 2.4 mol of manganese oxalate, and 0.8 mol of manganese tetraoxide, and finally obtains lithium manganese iron phosphate material.
[0056] Example 3
[0057] The difference from Example 1 is that the total molar amount of manganese element is the same as that in Example 1, and the molar ratio of manganese sulfate, manganese acetate and manganese tetraoxide is 0.6:1.8:1.2, and finally lithium manganese iron phosphate material is obtained.
[0058] Example 4
[0059] The difference from Example 1 is that the total molar amount of manganese element is the same as that in Example 1, and the molar ratio of manganese sulfate, manganese acetate and manganese tetraoxide is 1.2:1.8:1, and finally lithium manganese iron phosphate material is obtained.
[0060] Example 5
[0061] The difference from Example 1 is that the total molar amount of manganese element is the same as that in Example 1, and the molar ratio of manganese sulfate, manganese acetate and manganese tetraoxide is 0.6:0.6:1.6, and finally lithium manganese iron phosphate material is obtained.
[0062] Example 6
[0063] The difference from Example 1 is that the ratio of glucose: polyethylene glycol 6000: citric acid is 6:2:2, and lithium manganese iron phosphate material is finally obtained.
[0064] Example 7
[0065] The difference from Example 1 is that the ratio of glucose: polyethylene glycol 6000: citric acid is 8:1:1, and lithium manganese iron phosphate material is finally obtained.
[0066] Example 8
[0067] The difference from Example 1 is that the carbon sources are all glucose, and lithium manganese iron phosphate material is finally obtained.
[0068] Example 9
[0069] The difference from Example 1 is that the solid content of the liquid (I) is 40%, and lithium manganese iron phosphate material is finally obtained.
[0070] Example 10
[0071] The difference from Example 1 is that the solid content of the liquid (II) is 40%, and lithium manganese iron phosphate material is finally obtained.
[0072] Embodiment 11
[0073] The difference from Example 1 is that during the low-temperature heat treatment, the temperature is raised to 200°C and kept for 2 hours, during the medium-temperature heat treatment, the temperature is continued to be raised to 450°C and kept for 5 hours, and during the high-temperature heat treatment, the temperature is continued to be raised to 750°C and kept for 5 hours; after the material is cooled to 50°C, it is air flow crushed and the particle size D50 is controlled to be 0.8-1μm, and finally lithium manganese iron phosphate material is obtained.
[0074] Example 12
[0075] The difference from Example 1 is that the heat treatment is carried out at 650° C. for 8 hours from the beginning to the end, and finally the lithium manganese iron phosphate material is obtained.
[0076] Example 13
[0077] The difference from Example 1 is that the carbon source is replaced with (glucose: polyethylene glycol 6000=8:2), and finally lithium manganese iron phosphate material is obtained.
[0078] Embodiment 14
[0079] The difference from Example 1 is that the carbon source is replaced with (glucose: polyethylene glycol 6000=7:3), and finally lithium manganese iron phosphate material is obtained.
[0080] Embodiment 15
[0081] The difference from Example 1 is that the temperature of the third stage is changed from 720° C. to 750° C., and finally lithium manganese iron phosphate material is obtained.
[0082] Example 16
[0083] The difference from Example 1 is that during the sintering process, the temperature is directly raised to 720° C. and kept for 5 hours to finally obtain lithium manganese iron phosphate material.
[0084] Comparative Example 1
[0085] The difference from Example 1 is that manganese source 1, manganese source 2 and manganese source 3 are all manganese tetraoxide, and lithium iron manganese phosphate material is finally obtained.
[0086] Comparative Example 2
[0087] The difference from Example 1 is that manganese source 1, manganese source 2 and manganese source 3 are all manganese sulfate, and lithium iron manganese phosphate material is finally obtained.
[0088] Comparative Example 3
[0089] The difference from Example 1 is that the feed solution (I), the feed solution (II) and 10.15 mol of lithium hydroxide are mixed and then ground by a sand mill to finally obtain lithium iron manganese phosphate material.
[0090] Performance Testing
[0091] The lithium iron manganese phosphate materials of the above-mentioned embodiment and the comparative example are taken respectively, and the lithium iron manganese phosphate material, conductive carbon black (Super P), carbon nanotubes, and a binder (polyvinylidene fluoride) are mixed evenly in a mass ratio of 90:3:2:5, ground sufficiently, and N-methylpyrrolidone is added. Then, the mixture is placed in a vacuum ball mill and ball-milled at a speed of 600 r / min for 2 h to obtain a paste-like positive electrode slurry with a viscosity of 2000 to 4000 mPa·s; then, the positive electrode slurry prepared above is coated on the surface of an aluminum foil current collector with a thickness of 14 μm by a coating machine, and the coating thickness is set to 350 μm, and then baked at 120°C to form a positive electrode active material layer, and then cold-pressed to a corresponding thickness by a roller press to obtain a positive electrode sheet.
[0092] The above positive electrode sheet and lithium sheet were used as the positive electrode and reference electrode of the lithium-ion battery respectively, Celgard 2400 was used as the separator, and a mixed solution of 1 mol / L LiPF6 EC and EMC (v / v=1:1) was used as the electrolyte solution. The button cells were assembled for testing, and other physical parameters were tested. The specific test results are shown in Table 1.
[0093] Table 1
[0094]
[0095]
[0096] Combined with the contents of Table 1, the following conclusions can be verified: Referring to Examples 1 and 2, the comprehensive performance is better than that of Comparative Examples 1 and 2, proving that the use of three different types of manganese source solutions in this embodiment effectively improves the gram capacity and compaction density of the lithium manganese iron phosphate material.
[0097] By comparing Examples 1, 6, 7, 8, 13 and 14, it is demonstrated that the synergistic effect of different carbon sources is helpful to the performance of the material.
[0098] By comparing Examples 11, 12, 15 and Example 16, it can be seen that appropriate temperature and sintering process are required to ensure a balance between the electrical properties and compaction of the lithium manganese iron phosphate material.
[0099] By comparing Examples 1, 3 to 5, it can be seen that when the molar ratio of manganese sulfate, manganese acetate and manganese tetraoxide is outside the range of (1 to 3): (3 to 5): (4 to 6), it has little effect on the compaction density of the lithium manganese iron phosphate material, but will reduce the electrical properties of the lithium manganese iron phosphate material.
[0100] Figure 2 The SEM image of the lithium iron manganese phosphate material in Example 1 is shown. Figure 2 It can be seen from the examples that there is an obvious gradation of large and small particles, which is attributed to the use of three manganese source precursors with different morphologies. During the sintering process, iron atoms will gradually blend into the manganese source to form a gradation based on the manganese source, thereby increasing the overall compaction density of the material. Figure 2 It can also be seen from the comparison of the compaction density curves of the lithium manganese iron phosphate materials prepared in Example 1 and Comparative Examples 1 to 3 that the compaction density is significantly improved.
[0101] It can be seen from the above table that the lithium manganese iron phosphate product prepared by the preparation method provided by the present invention is superior to the related products in the comparative example in terms of multiple parameters such as first charge, first effect, compaction density, specific surface area, capacity at 0.2C, and compaction density.
[0102] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:
[0103] The present application is based on the diffusion difference between manganese ions and iron ions in the olivine skeleton structure during heat treatment (iron ions are integrated into the manganese source). On the one hand, by adopting three manganese sources with different crystal structures and morphologies, a lithium iron manganese phosphate material with excellent electrical properties and high compaction density is prepared through a one-time sand milling and a one-time sintering process, thereby improving the performance of the lithium iron manganese phosphate material while also being beneficial to the formation of particle grading and the improvement of sand milling efficiency; on the other hand, mixing the carbon source alone with the sand milled slurry can avoid the problem of carbon source coating on the particle surface hindering the effective collision of zirconium balls and the reduction of grinding efficiency caused by slurry thickening during grinding, and can ensure the accuracy of the material particle size test after sand milling; on the other hand, mixing the lithium source with the spray material can avoid the problem of lithium ions combining with phosphate to form precipitates and causing unstable particle size monitoring; therefore, the preparation method of the present application does not require high requirements for the sand mill, nor will it produce high energy consumption as caused by traditional processes, that is, the preparation method and equipment of the lithium iron manganese phosphate material in the present application are simple, lower cost, and more conducive to industrial large-scale production.
[0104] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing lithium manganese iron phosphate material, characterized in that: The preparation method comprises: Step S1, sand-milling the raw materials including the iron source, the first manganese source, the second manganese source, the third manganese source and the phosphorus source to obtain a sand-milled material; Step S2, mixing the sand-milled material with a carbon source to obtain a mixture; Step S3, spraying the mixture to obtain a spray material, and mixing the spray material with a lithium source to obtain a mixed lithium yellow material; Step S4, in an inert atmosphere, heat-treating and crushing the mixed lithium yellow material in sequence to obtain a lithium iron manganese phosphate material; Wherein, the first manganese source is an inorganic water-soluble manganese compound, the second manganese source is an organic manganese source, and the third manganese source is a manganese oxide.
2. The preparation method according to claim 1, characterized in that: In step S1, the first manganese source is selected from any one or more of manganese sulfate, manganese nitrate, manganese chloride and manganese dihydrogen phosphate; and / or the second manganese source is selected from any one or more of manganese oxalate, manganese acetate, manganese citrate, manganese glycinate and manganese gluconate; and / or the third manganese source is selected from any one or more of manganese oxide, manganese dioxide, manganese trioxide and manganese tetraoxide.
3. The preparation method according to claim 1 or 2, characterized in that: The molar ratio of manganese element among the first manganese source, the second manganese source and the third manganese source is (1-3): (3-5): (4-6).
4. The preparation method according to any one of claims 1 to 3, characterized in that The D50 particle size of the material after sand grinding is 0.48 μm to 0.50 μm.
5. The preparation method according to any one of claims 1 to 4, characterized in that: In step S1, the raw material further includes a first solvent, and the first solvent is selected from any one or more of water, ethanol, methanol and glycerol; and / or the solid content of the raw material is 30% to 50%.
6. The preparation method according to any one of claims 1 to 5, characterized in that In step S1, the phosphorus source is selected from any one or more of phosphoric acid, ammonium dihydrogen phosphate, diammonium hydrogen phosphate and phosphorus pentoxide; and / or the iron source is selected from any one or more of ferric phosphate, ferric phosphate, ferric oxalate, ferric oxide, ferrous oxide, ferric hydroxide, ferrosoferric oxide and ferric acetate.
7. The preparation method according to any one of claims 1 to 6, characterized in that In step S2, the carbon source includes a first carbon source and a second carbon source; the mass ratio of the first carbon source to the second carbon source is (6-8): (2-4), and / or the first carbon source is selected from any one or more of glucose, sucrose, maltose, starch and fructose; and / or the second carbon source is selected from any one or more of citric acid, tannic acid, ascorbic acid, polyacrylic acid, polyvinyl alcohol, xylitol and polyethylene glycol.
8. The preparation method according to any one of claims 1 to 6, characterized in that In step S2, the mixture further comprises a second solvent, and the second solvent is selected from any one or more of water, ethanol, methanol and isopropanol; And / or the solid content of the mixture is 30% to 50%.
9. The preparation method according to any one of claims 1 to 8, characterized in that: In step S4, the heat treatment includes low temperature heat treatment, medium temperature heat treatment and high temperature heat treatment performed sequentially; and / or the heating rate during the heat treatment process is 60°C / h to 180°C / h; and / or the temperature of the low temperature heat treatment is 100° C. to 200° C., and the time of the low temperature heat treatment is 1 h to 2 h; and / or the temperature of the medium temperature heat treatment is 450° C. to 650° C., and the time of the medium temperature heat treatment is 3 h to 5 h; And / or the temperature of the high temperature heat treatment is 700°C to 750°C, and the time of the high temperature heat treatment is 5h to 8h.
10. A lithium manganese iron phosphate material, characterized in that: The lithium manganese iron phosphate material is prepared by the preparation method described in any one of claims 1 to 9.
Citation Information
Patent Citations
Positive material for lithium ion battery, preparation method of material, and lithium ion battery
CN103258994A
Lithium ferric manganese phosphate composite material and preparation method thereof
CN106505192A
Preparation method of high-compaction lithium ferric manganese phosphate positive electrode material
CN113659133A
Preparation method of lithium ferric manganese phosphate material
CN114583155A
Modified lithium iron manganese phosphate material, preparation method thereof and battery
CN115709976A